1998
DOI: 10.1093/ps/77.10.1481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary crude protein on growth, ammonia concentration, and litter composition in broilers

Abstract: An experiment was conducted to determine the effect of diets with reduced CP and supplemental amino acids on broiler performance, N excretion, litter characteristics, and equilibrium NH3 gas concentration. Results suggest that reducing CP (and lysine) below 241 g/kg (13.7 g/kg lysine) in the diets fed during the first 3 wk may slightly increase feed:gain and therefore may not be advisable. During the period 22 to 43 d of age there were no significant differences in weight gain and BW at 6 wk of age when reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
73
3
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 22 publications
14
73
3
7
Order By: Relevance
“…Crude protein was included in the model and an increased nitrogen excretion was related to greater excreta moisture content. This is in line with results reported by Ferguson et al (1998a) and Namroud et al (2008). Elevated dietary protein content (overformulation of diets) or an imbalanced amino acid profile has been identified as a cause of wet litter (Collet, 2006;Namroud et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Crude protein was included in the model and an increased nitrogen excretion was related to greater excreta moisture content. This is in line with results reported by Ferguson et al (1998a) and Namroud et al (2008). Elevated dietary protein content (overformulation of diets) or an imbalanced amino acid profile has been identified as a cause of wet litter (Collet, 2006;Namroud et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been observed by Hussein et al (2001) and Bregendahl et al (2002), i.e., that reported decreased performance of birds fed lowprotein diets. Other studies have also reported that protein levels had no effects on feed intake (Ferguson et al, 1998;Araújo, 2001). Gonzales (2002) stated that the diet intake control is affected not only by the protein content, but also by protein quality, i.e., amino acid balance.…”
Section: Resultsmentioning
confidence: 96%
“…A high level of crude protein has a negative effect on the quality of the sawdust, as confirmed by the results of Ferguson et al (1998) which show that content of moisture has increased with increasing protein content in the mixtures.…”
Section: Introductionmentioning
confidence: 53%
“…Results of Ferguson et al (1998) indicate that the increase in protein content in the mixtures resulted an increase moisture content in the sawdust, which caused a greater frequency of the lesions on foot pads.…”
Section: Resultsmentioning
confidence: 98%